Fungicide sensitivity of two Colletotrichum species pathogenic to rubber - Jayasinghe C K; Fernando T H P S (International Journal of Tropical Plant Diseases, 2000)
Colletotrichum acutatum, pathogen tolerates high levels of three common fungicides namely; benomyl, carbendazim and thio-phanate methyl was shown to be highly sensitive to tubuconazole (EC100 = 5mg/ml), bitertanol (EC100 = 50mg/ml), epoxiconazole (EC100 = 200mg/ml) and propiconazole (EC100 = mg/ml). The conidial germination of C.acutatum was totally inhibited (EC100) by captan (1mg/ml), propineb 56;+ oxadixyl 10;(5mg/ml) and thiram (2mg/ml). With regard to Colletotrichum gloeosporioides, the mycelial growth was completely checked (EC100) by benomyl (5mg/ml), carbendazium (5mg/ml), thiophanate methyl (50mg/ml) and epoxiconazole (100mg/ml) while conidial germination was highly snsitive to captan (EC100 = 1mg/ml), copper 21;+ manacobez 20;(EC 100 = 5mg/ml), and thiram (EC100 = 5mg/ml). Analysis of the results showed that it is appropriate to identify a combination of potential fungicides, spore germination inhibitor and a chemical effective in checking mycelial growth in management of Colletotrichum leaf disease (CLD) on rubber as both these species are responsible in causing CLD in Sri Lanka. The ideal combination appeared to be captain and tebuconazole as conidia of both species were found to be extremely sensitive to captan (EC100 = 1mg/ml) and the fungicide tebuconazole checked the mycelial growth of C. acutatum & C. gloeosporioides at markedly low concentrations of 5 & 50 mg/ml respectively.
Keywords: Collectotrichum acutatum; Colletotrichum gloeosporioides; Fungicide sensitivity; Hevea brasiliensis